Evaluation of the public-private partnership in the Lekgalameetse Nature Reserve : Maruleng Municipality in the Limpopo Province - Mashale, Modise Christopher (University of Limpopo, 2014)
The aim of the study was to examine the public private partnership in Lekgalammetse Nature Reserve, which was championed by the Limpopo Tourism Agency under the banner of Limpopo Economic Development Environment and Tourism Department after the protected land was placed under restitution process. The purpose of the study was to evaluate whether the partnership which was created has the capacity to enhance the socio-economic development of the claimants and the adjacent communities in the area where the nature reserve is situated. Land restitution process in case of an area declared protected area by law; says that there will not be physical occupation by the claimants in terms of section 42 of the Land Restitution Act. Therefore the only way that the claimants can benefit from the land, is to become land owners and partner in terms of activities that take place in the protected area for social and economic benefits. A public private partnership was recognised as a potential vehicle for social, economical and environmental well being of both parties. However the developmental prospects of the partnership were unknown and overestimated. Views from the study as well as the literature review support the assertions that in this type of land claim, a public private partnership is the best way to go about developing the claimants and the adjacent communities. The review also highlighted the importance of a partnership in a protected area and its benefits, especially in developing the adjacent communities. Thus the role of the community in participating in their development and of the protected area was the main focus of this study. The study collected both qualitative and quantitative data using interviews and a questionnaire. The study concluded by providing recommendations to stakeholders of Lekgalameetse Nature Reserve on how to improve their partnership relations. Some of the recommendations proposed are to involve a private partner to enhance development in the area; there should be provided with a coordinated and proper management, develop a capacity building tool to improve the co-management function and create an environment where all partners are equal in the partnership. The correct implementation of the Performance Management System will serve as a means to enhance organizational efficiency, effectiveness and accountability in the use of resources in accelerating access to good quality services and a better life for all. A well balanced partnership has a potential to increase community benefits and maximize the conservation of the biodiversity of the area.
Thesis (M. Dev.) -- University of Limpopo, 2014
Keywords: Public private partnerships; Economic development; Tourism; Economic development projects -- Evaluation